Blockchain: A Tale of Two Applications - Ferreira, Micael (2018)
Bitcoin continues to get more and more attention from the media, mainly because of the volatility of its value and insignificantly associated with the technological innovation. This cryptocurrency is supported by an immutable database and is distributed throughout a network of thousands of nodes, known as Blockchain. One way to ensure that all the concepts behind the Blockchain technology and infrastructure are seized is to conduct the development of one of the most popular context applications for it: a wallet for well-known cryptocurrencies. Yet Another Bitcoin Wallet (YABW) is a hybrid application available for both Android and iOS, which was developed with the Ionic and Angular frameworks. This application communicates with Bitcoin Blockchain to send, receive and store bitcoins; provides a set of features focused on security and user experience, and is available on the Play Store and Apple Store. A rather relevant issue that is becoming a major subject of current research is the application of the Blockchain infrastructure to other contexts that are neither directly connected to cryptocurrencies, nor are finance related. The implementation of a proof-of-concept application proposes the use of a blockchain for a specific case study: the exchange of meal vouchers of an institution amongst students. This is achieved using the decentralized platform Ethereum, which allows us to create a Smart Contract using the Solidity programming language to create a token that follows the Ethereum Request for Comment (ERC), the ERC-20 standard and represents the meal vouchers. This second application uses the architecture defined for YABW, reusing major components and custom developing specific modules to enhance the required features. There is still a lot of research to be done on the non-financial applicability of the Blockchain infrastructure and technology, but for the moment, we have left further evidence that it is possible and is a relative straight-forward process to accomplish from the technological perspective.